The Predictive Effect of Parental Adult Attachment on Parent–Adolescent Attachment: The Mediating Role of Harsh Parenting - Li, Mengge; Chen, Xin; Gong, Huoliang; Ji, Wanghua; Wang, Wei; Liang, Shifeng; Kong, Anran (Frontiers in Psychology, 2021)
This study examines the relationship between parental adult attachment and parent–adolescent attachment and investigates the mediating role of harsh parenting from the perspective of family systems theory. The sample included adolescents and their parents from 1,030 families in Henan Province, China. Measures included the Experiences in Close Relationships Scale, Inventory of Parent and Peer Attachment Scale, and Harsh Parenting Scale. The results showed that paternal avoidance negatively predicts father–adolescent and mother–adolescent attachments, while maternal avoidance and maternal anxiety negatively predict father–adolescent attachment and mother–adolescent attachment, respectively. Paternal harsh parenting not only mediated the relationship between paternal adult and father–adolescent attachment but also between paternal adult and mother–adolescent attachment. However, maternal harsh parenting only plays an intermediary role between maternal adult and mother–adolescent attachment. The results of the study show that compared with the adverse effects of maternal adult attachment and maternal harsh parenting on parent–adolescent attachment, paternal avoidance and paternal harsh parenting more negatively affect parent–adolescent attachment, which is not conducive to familial harmony.